International trends in the reading of the Muslim population of the Omsk region - N. V. Ogurtsova (Библиосфера)
This article contains empirical data on peculiarities of national literature reading by Muslim population in the Omsk region according to four criteria: sex, age, educational level, mixed or homogeneous marriages.